2005
DOI: 10.1073/pnas.0501784102
|View full text |Cite
|
Sign up to set email alerts
|

Xantha-l encodes a membrane subunit of the aerobic Mg-protoporphyrin IX monomethyl ester cyclase involved in chlorophyll biosynthesis

Abstract: Chlorophyll biosynthesis is a process involving Ϸ20 different enzymatic steps. Half of these steps are common to the biosynthesis of other tetrapyrroles, such as heme. One of the least understood enzymatic steps is formation of the isocyclic ring, which is a characteristic feature of all (bacterio)chlorophyll molecules. In chloroplasts, formation of the isocyclic ring is an aerobic reaction catalyzed by Mg-protoporphyrin IX monomethyl ester cyclase. An in vitro assay for the aerobic cyclase reaction required m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
105
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(109 citation statements)
references
References 30 publications
3
105
1
Order By: Relevance
“…It has long been believed that the O 2 -dependent cyclase reaction requires NAD(P)H as a reductant (5), with dependence observed in plant, algal, and cyanobacterial systems (20,40). The barley xantha-l and viridis-k mutants that accumulate MgPME are deficient in the membrane components of the O 2 -dependent enzyme, with all xantha-l mutations mapping to the single acsF ortholog that is intact in the viridis-k mutants (11). Subsequently, Bollivar et al (41) concluded that viridis-k mutants do not lack Ycf54; thus, it is possible that the missing subunit of the enzyme, disrupted in viridis-k mutants, is a membrane-associated NAD(P)H-binding protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has long been believed that the O 2 -dependent cyclase reaction requires NAD(P)H as a reductant (5), with dependence observed in plant, algal, and cyanobacterial systems (20,40). The barley xantha-l and viridis-k mutants that accumulate MgPME are deficient in the membrane components of the O 2 -dependent enzyme, with all xantha-l mutations mapping to the single acsF ortholog that is intact in the viridis-k mutants (11). Subsequently, Bollivar et al (41) concluded that viridis-k mutants do not lack Ycf54; thus, it is possible that the missing subunit of the enzyme, disrupted in viridis-k mutants, is a membrane-associated NAD(P)H-binding protein.…”
Section: Discussionmentioning
confidence: 99%
“…gelatinosus contains both BchE and AcsF cyclases, conferring the ability to synthesize BChl under varying O 2 regimes (9). Orthologs of acsF are widely distributed in phototrophs and have been studied in higher plants (10,11), algae (12) and cyanobacteria (13), the green nonsulfur bacterium Chloroflexus aurantiacus (14), and the purple alphaproteobacterium Rhodobacter (Rba.) sphaeroides (15) (Fig.…”
mentioning
confidence: 99%
“…In the anaerobic cyclase the 13 1 -oxo group of bacteriochlorophyll is derived from water (13), whereas in aerobic phototrophs such as Roseobacter denitrificans this group arises from molecular oxygen (14). Partial purification of oxidative cyclase from chloroplasts and cyanobacteria suggested that this enzyme requires several proteins (subunits) for activity (6,15). The only known candidate for a catalytic cyclase subunit was identified by mutational analysis of the photosynthetic bacterium Rubrivivax gelatinosus.…”
mentioning
confidence: 99%
“…Thus, R. gelatinosus possesses two unrelated MgPME cyclases, one oxygen-dependent and one oxygen-independent (16,17). AcsF homologs have since been identified in many photosynthetic eukaryotes including C. reinhardtii (18), Arabidopsis thaliana (19), and barley (15). Two acsF-like genes, sll1214 and sll1874, have been identified in Synechocystis PCC 6803 (hereafter Synechocystis) (20); Sll1214 is essential for growth under aerobic conditions (20) and, to a certain extent, micro-oxic conditions (21), whereas Sll1874 was found to be essential for growth in micro-oxic conditions (20,21).…”
mentioning
confidence: 99%
“…The Albina and Xantha barley plants carrying a mutation preventing chloroplast development are suitable for analysis of the roles of chloroplast in salt stress response. Although these mutations are lethal, the large seed endosperm can support plant growth for several weeks, allowing studies on these mutants (Dal Bosco et al 2003, Olsson et al 2004, Rzeznicka et al 2005, Svensson et al 2006, Campoli et al 2009, Müller and Hansson 2009. To investigate the roles of chloroplast development in formation of salt tolerance in barley, the nonallelic Albina and Xantha mutants were exposed to soil salinity (200 mmol) for 6 days and the stomatal performance, Na + /K + homeostasis and ROS metabolism were analysed.…”
mentioning
confidence: 99%